2013
DOI: 10.1103/physreva.87.043822
|View full text |Cite
|
Sign up to set email alerts
|

Bright extreme-ultraviolet high-order-harmonic radiation from optimized pulse compression in short hollow waveguides

Abstract: Multimodal nonlinear propagation dominates the evolution of intense laser pulses propagating in high pressure gas-filled capillaries used for high harmonic generation. A fully multimodal nonlinear propagation model is used to predict pulse evolution along such a capillary, and the length and pressure distribution optimised to produce the shortest pulses at the capillary output. This optimisation is shown theoretically to result in self compression of the pulse from ∼53 fs to ∼7 fs, and shown experimentally to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…The fused-silica fiber design used here was 50 mm in length with a hollow core diameter of 150 µm and was assumed to be homogeneously filled with 100 mbar of argon. These parameters are consistent with those used in our experimental work [10,22].…”
Section: A An Initial Simulation and Physical Mechanismssupporting
confidence: 90%
See 3 more Smart Citations
“…The fused-silica fiber design used here was 50 mm in length with a hollow core diameter of 150 µm and was assumed to be homogeneously filled with 100 mbar of argon. These parameters are consistent with those used in our experimental work [10,22].…”
Section: A An Initial Simulation and Physical Mechanismssupporting
confidence: 90%
“…4(c)). It has been suggested that by analysing the high harmonic spectrum in the far-field these could be verified experimentally [33], and in fact we have recently demonstrated a similar approach in our experiments [10]. , (e) and (f) highlight these properties as a function of the input pulse energy.…”
Section: A An Initial Simulation and Physical Mechanismssupporting
confidence: 75%
See 2 more Smart Citations
“…These simulations are based on a multimode generalized nonlinear Schrödinger equation [17] that accounts for mode dispersion, nonlinear Kerr and Raman effects, self-steepening, ionization, plasma refractive index, and nonlinear mode coupling, which has been tested previously for high-power pulse propagation in short capillaries [18,19]. The lowest 15 transverse modes with rotational symmetry were included in the simulations (for details of mode calculations and sample dispersion curves see Sec.…”
Section: Numerical Simulationsmentioning
confidence: 99%